LEGAL MEASURE CONCERNING OF ENFORCEMENT FISHERIES LAW AND THE CONSERVATION OF MARINE ENVIRONMENT IN TAKAT NGAO, THA MAI CHANTHABURI - Kerdnaimongkol, Saphayasit; Pramarn, Songporn; Ittimecha, Thitirat; Ployjun, Somjate (Rangsit Journal of Law and Society, 2024)
The study of data in the Takat Ngao community found that the number of local fishing boats has increased, both legally and illegally registered. There has been more competition to catch aquatic animals for a living. In addition, there is limited space for boats due to the villagers' excessive oyster farming, which has resulted in shallow rivers and canals that are navigable in some areas. Therefore, there must be measures to determine the areas for oyster farming in proportion and to leave space between waterways for fishing boats. In addition, the problem affecting marine resources resulting from fishing occupations that illegally catch aquatic animals beyond the legal limit, without considering the degradation of marine resources or the imbalance of the ecosystem. It was the documentary research that has the purpose is to study the relevant laws and analyze them to find solutions to the problem at the right point. The results of the research found that villagers in the Takad Ngao community cultivate oysters in the canals beyond the balance of nature, resulting in shallow canals that have a significant impact on villagers who work as fishermen. However, the villagers' fishing occupations have also caused marine resources to deteriorate as well, because relevant government agencies cannot control the number of boats and the amount of aquatic animals caught, which is considered a lack of efficiency in coastal fisheries management.